The Role of Modern Harvesting Tools in Supporting Agricultural Modernization and National Food Security - Judijanto, Loso; Suparwata, Dewa Oka; Marjan, M; Andriyani, Liz Yanti (West Science Agro, 2025)
Modern harvesting tools have become essential in supporting agricultural modernization and strengthening food security in Indonesia. This study uses a qualitative approach, interviewing five farmers to explore their experiences with adopting and utilizing these tools. The findings reveal that modern harvesting tools significantly reduce labor requirements, save time, and improve crop quality, directly benefiting farmers' productivity. However, the adoption process is hindered by financial constraints, limited technical knowledge, and maintenance challenges. The study highlights the need for government support in providing subsidies, affordable credit, and local technical training to ensure the sustainable use of modern tools. These findings underscore the transformative potential of modern agricultural technologies in achieving national food security goals.